The Effect of the COVID-19 Pandemic on Discipline Character Habituation in Students at SD Muhammadiyah 1 Sidoarjo - Mohammad Ilham Dzulfikar; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This research is motivated because there are some students who experience a decrease in discipline during online learning, both in participating in online learning, collecting homework, and other things. This study aims to determine the effect of the Covid-19 pandemic on the habituation of the discipline character of students at SD Muhammadiyah 1 Sidoarjo. This study uses a qualitative research method with a descriptive analytycs approach, where the research is carried out in stages starting with determining the topic, collecting data, analyzing data. Information was collected by interviewing teachers and principals of SD Muhammadiyah 1 Sidoarjo on matters relevant to the research. The results showed that learning with an online system during the pandemic was considered to have a relatively sufficient impact on student discipline habituation with the existence of systematic activities from teachers, namely program planning, monitoring, and evaluation. This systematic activity was carried out to improve a good personality and to cultivate disciplined character for students of SD Muhammadiyah 1 Sidoarjo.